2008
DOI: 10.2147/copd.s4177
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of amoxycillin versus amoxycillin/clavulanate in acute exacerbations of chronic pulmonary obstructive disease in primary care

Abstract: Background: Amoxycillin/clavulanate is considered fi rst-line treatment for ambulatory exacerbations of COPD. However, narrow-spectrum antibiotics may be as useful for mild to moderate patients. Objective: To compare the clinical effi cacy of amoxycillin versus amoxicyllin/clavulanate in exacerbations of COPD in primary care. Methods: A randomized, double-blind, noninferiority clinical trial was carried out in eight primary care centers in Catalonia, Spain. Spirometrically-diagnosed patients older than 40 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
3
0
1
Order By: Relevance
“…We would like to thank Lisa Pastore for her outstanding editorial contributions to this manuscript. Conflict of Interest: The authors have indicated the following relationships: Timothy AlbertsonFSpeaker Honorarium: Boehringer Ingelheim and GlaxoSmithKline on topic of COPD, Anzueto et al 67 58.3, 57.2 CL-extend (1,000 qd  7 d) A/C (875 bid  10 d) CCF85% vs 87% (NS) AEF20% vs 24% (NS) Adverse gastrointestinal severity score 4A/C than CL-exten (P 5 0.016) Llor et al 68 71.9, 70.8 A (500 tid  10 d) A/C (500/125 tid  10 d) CCF90.9% vs. 92.8% (NS) AEF4.4% vs. 11.6% (NS) Petitpretz et al 69 64.3, 64.2 L (500 qd  10 d) Cef (250 bid  10 d) CCF94.6% vs 93.3% (NS) No difference RRR Amsden et al 70 58. 74 55.5, 56.4 M (400 qd  5d) Az (500 qd  3 d) CCF82% vs 81% (NS) Equal microbiological eradication Grassi et al 75 69.6, 69.1 M (400 qd  5d) Ceft (1,000 qd  7 d) CCF90.6% vs 89.0% (NS) Equal microbiological eradication Cost savings with M vs Ceft Schaberg et al 76 61.3, 59.3 M (400 qd  5d) A/C (625 tid  7 d) CCF96.2% vs 91.6% (NS) Equal microbiological eradication Wilson et al 66 68.1, 67.1 G (320 qd  5d) Ceft (1,000 qd  1-3 d) followed by Cef (500 bid 4-6 d) maximum 7 d total treatment CCF82.6% vs 72.1% (Po.05) G 9 d vs Ceft/Cef 11 d to hospital discharge, (P 5.04) Equal microbiological eradication à All doses 5 mg.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…We would like to thank Lisa Pastore for her outstanding editorial contributions to this manuscript. Conflict of Interest: The authors have indicated the following relationships: Timothy AlbertsonFSpeaker Honorarium: Boehringer Ingelheim and GlaxoSmithKline on topic of COPD, Anzueto et al 67 58.3, 57.2 CL-extend (1,000 qd  7 d) A/C (875 bid  10 d) CCF85% vs 87% (NS) AEF20% vs 24% (NS) Adverse gastrointestinal severity score 4A/C than CL-exten (P 5 0.016) Llor et al 68 71.9, 70.8 A (500 tid  10 d) A/C (500/125 tid  10 d) CCF90.9% vs. 92.8% (NS) AEF4.4% vs. 11.6% (NS) Petitpretz et al 69 64.3, 64.2 L (500 qd  10 d) Cef (250 bid  10 d) CCF94.6% vs 93.3% (NS) No difference RRR Amsden et al 70 58. 74 55.5, 56.4 M (400 qd  5d) Az (500 qd  3 d) CCF82% vs 81% (NS) Equal microbiological eradication Grassi et al 75 69.6, 69.1 M (400 qd  5d) Ceft (1,000 qd  7 d) CCF90.6% vs 89.0% (NS) Equal microbiological eradication Cost savings with M vs Ceft Schaberg et al 76 61.3, 59.3 M (400 qd  5d) A/C (625 tid  7 d) CCF96.2% vs 91.6% (NS) Equal microbiological eradication Wilson et al 66 68.1, 67.1 G (320 qd  5d) Ceft (1,000 qd  1-3 d) followed by Cef (500 bid 4-6 d) maximum 7 d total treatment CCF82.6% vs 72.1% (Po.05) G 9 d vs Ceft/Cef 11 d to hospital discharge, (P 5.04) Equal microbiological eradication à All doses 5 mg.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Thirty-four RCTs included 45 descriptive instruments [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. All but three trials were deemed to be at high risk of methodological bias.…”
Section: Resultsmentioning
confidence: 99%
“…Few studies compare the use of AMX instead of AMC in AECOPD, without also looking at other antibiotics at the same time in a small-spectred vs. broad-spectred analysis. We identified one article [ 30 ] that directly compares AMX with AMC in AECOPD. It was conducted prospectively in 137 patients in an outpatient setting and did not find any difference in outcome (clinical cure assessed by a physical examination on day 10 and 30).…”
Section: Discussionmentioning
confidence: 99%